ANALISIS DEFORMASI KOLOM TANAH GRANULAR MENGGUNAKAN METODE SMOOTHED PARTICLE HYDRODYNAMICS - Aulina Reza Putri; Wiwik Rahayu; R. R. Dwinanti Rika Marthanty (LPPM Universitas Abdurrab, 2024)
Large magnitude earthquakes often trigger liquefaction phenomenon in granular soil deposits. One of the major liquefaction events in Indonesia occurred during the 2018 Palu earthquake, which caused economic losses around 1.1 billion USD. Liquefaction can be mitigated by evaluating the risk and impact it will cause. The events can be modeled numerically by using the SPH method. SPH is a continuum method that doesn’t need to simulate numerical model. The advantage of using SPH is its ability to model large deformation phenomenon using Lagrangian approach. In this research, SPH was used to model the failure mechanism of 2D saturated granular soil column with 0.6 m x 2.0 m dimension. Soil constitutive model used is elasto-plastic, where plastic deformation is measured using Drucker-Prager failure criterion. The interaction between soil-water particles is represented by the seepage force, following the research model of Korzani et al. (2017). In this model, no external forces applied other than the gravity force. The simulation results are used to analyze granular soil deformation.